Gillnet fishers' knowledge reveals seasonality in depth and habitat use of cod (Gadus morhua) in the Western Baltic Sea. (7th May 2020) - Funk, Steffen; Krumme, Uwe; Temming, Axel; Möllmann, Christian
Abstract: Practical and applied knowledge of local fishers can help to improve our understanding of target species ecology and fisheries management decisions. In the Western Baltic Sea (WBS), the spatio-temporal distribution of cod is still largely unknown despite decades of research. We studied changes in cod distribution by obtaining information on temporal depth and habitat use of cod from commercial gillnet fishers using semi-directed interviews supplemented by at-sea observer data. Linear and non-linear regression analyses revealed significant relationships between depth use of cod and sea surface temperature (SST) as well as thermal stratification. Moreover, habitat use was related to SST and residence depth of cod. Areas deeper than 15 m were favoured from late December until March during low SST and a mixed water column (spawning) and also from July until August during high SST and strong thermal stratification (summer aestivation). Shallower areas were favoured during the rest of the year. The depth and habitat use displayed distinct seasonal up- and downslope movements of cod. This study highlights the importance of shallow-water and structured habitats for cod in the WBS and the value of local knowledge held by fishers for a better understanding of the distributional dynamics of important marine resource populations.